More Than Marketing: Inclusive Content and Customer Engagement in Disability-Oriented MSMEs on Instagram - Kurniawan Prasetyo; Andi Pajolloi Bate; Muhamad Iqbal (Mediator: Jurnal Komunikasi, 2025)
This study investigates the role of inclusive content in enhancing customer engagement for disability-oriented MSMEs in Indonesia, using @sunyicoffee on Instagram as a case study. Despite the growing demand for inclusive marketing, little quantitative evidence exists on its impact, especially in non-Western contexts. Adopting a cross-sectional quantitative survey design, the study collected data from 400 Instagram followers and analyzed it using simple regression to measure inclusive content dimensions and customer engagement indicators. The results revealed that inclusive content significantly influences five engagement dimensions: enthusiasm, attention, absorption, interaction, and identification. Key mechanisms include emotional resonance, authentic representation, inclusive language, accessible design, and shared values. The findings validate inclusive communication as a relational, not just representational, strategy, highlighting its capacity to convert audiences into community participants. This research offers theoretical implications by positioning inclusive content as a driver of relational engagement and practical insights for MSMEs aiming to build a sustainable digital community. Future research is encouraged to explore cross-platform applications and expand to broader cultural contexts.